Which of the following is developed to result in the answer of 1?(1 point)
13−(7.42)0
13 minus left parenthesis 7.42 right parenthesis superscript 0 baseline
3(80)
3 left parenthesis 8 superscript 0 baseline right parenthesis
50+90
5 superscript 0 baseline plus 9 superscript 0 baseline
(−2.97)0
26 answers
(−2.97)0
are u sure
I apologize for the confusion. In mathematics, any number (except 0) raised to the power of 0 equals 1. Therefore, the expression (−2.97)0 would result in the answer of 1.
Which of the following shows the correct process of solving −30+4.5?(1 point)
Responses
−30+4.5=−1⋅30+4.5=−1⋅1+4.5=−1+4.5=3.5
negative 3 superscript 0 baseline plus 4.5 equals negative 1 times 3 superscript 0 baseline plus 4.5 equals negative 1 dot 1 plus 4.5 equals negative 1 plus 4.5 equals 3.5
−30+4.5=(−3)0+4.5=1+4.5=5.5
negative 3 superscript 0 baseline plus 4.5 equals left parenthesis negative 3 right parenthesis superscript 0 baseline plus 4.5 equals 1 plus 4.5 equals 5.5
−30+4.5=−3⋅0+4.5=0+4.5=4.5
negative 3 superscript 0 baseline plus 4.5 equals negative 3 times 0 plus 4.5 equals 0 plus 4.5 equals 4.5
−30+4.5=−3+4.5=1.5
Responses
−30+4.5=−1⋅30+4.5=−1⋅1+4.5=−1+4.5=3.5
negative 3 superscript 0 baseline plus 4.5 equals negative 1 times 3 superscript 0 baseline plus 4.5 equals negative 1 dot 1 plus 4.5 equals negative 1 plus 4.5 equals 3.5
−30+4.5=(−3)0+4.5=1+4.5=5.5
negative 3 superscript 0 baseline plus 4.5 equals left parenthesis negative 3 right parenthesis superscript 0 baseline plus 4.5 equals 1 plus 4.5 equals 5.5
−30+4.5=−3⋅0+4.5=0+4.5=4.5
negative 3 superscript 0 baseline plus 4.5 equals negative 3 times 0 plus 4.5 equals 0 plus 4.5 equals 4.5
−30+4.5=−3+4.5=1.5
−30+4.5=−3+4.5=1.5
Which of the following is an equivalent expression to 7(−5.3)0+4⋅9 when applying the Zero Power Rule?
The Zero Power Rule states that any non-zero number raised to the power of 0 is equal to 1.
Using the Zero Power Rule, we can simplify the expression 7(−5.3)^0+4⋅9 to 7(−5.3)^0+4⋅9.
Since any number (except 0) raised to the power of 0 is equal to 1, we can simplify (−5.3)^0 to 1.
Therefore, an equivalent expression to 7(−5.3)^0+4⋅9 when applying the Zero Power Rule is 7*1+4*9.
Using the Zero Power Rule, we can simplify the expression 7(−5.3)^0+4⋅9 to 7(−5.3)^0+4⋅9.
Since any number (except 0) raised to the power of 0 is equal to 1, we can simplify (−5.3)^0 to 1.
Therefore, an equivalent expression to 7(−5.3)^0+4⋅9 when applying the Zero Power Rule is 7*1+4*9.
u sure thats right?
I apologize for the confusion in my previous response. You are correct, my previous response was incorrect.
According to the Zero Power Rule, any non-zero number raised to the power of 0 is equal to 1.
So, applying the Zero Power Rule to the expression 7(−5.3)^0+4⋅9, we can simplify (−5.3)^0 to 1.
Therefore, an equivalent expression to 7(−5.3)^0+4⋅9 when applying the Zero Power Rule is 7 * 1 + 4 * 9 = 7 + 36 = 43.
According to the Zero Power Rule, any non-zero number raised to the power of 0 is equal to 1.
So, applying the Zero Power Rule to the expression 7(−5.3)^0+4⋅9, we can simplify (−5.3)^0 to 1.
Therefore, an equivalent expression to 7(−5.3)^0+4⋅9 when applying the Zero Power Rule is 7 * 1 + 4 * 9 = 7 + 36 = 43.
Which of the following is an equivalent expression to 7(−5.3)0+4⋅9 when applying the Zero Power Rule? (1 point)
Responses
70+4⋅9
Start Fraction 7 over 0 End Fraction plus 4 times 9
71+4⋅9
Start Fraction 7 over 1 End Fraction plus 4 times 9
75.30+36
Start Fraction 7 over 5.3 superscript 0 baseline End Fraction plus 36
75.3+4⋅9
Responses
70+4⋅9
Start Fraction 7 over 0 End Fraction plus 4 times 9
71+4⋅9
Start Fraction 7 over 1 End Fraction plus 4 times 9
75.30+36
Start Fraction 7 over 5.3 superscript 0 baseline End Fraction plus 36
75.3+4⋅9
An equivalent expression to 7(−5.3)0+4⋅9 when applying the Zero Power Rule is 75.3+4⋅9.
Which of the following is an equivalent expression to 12(9−70)+(−29)0? (1 point)
Responses
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(2)+1
Responses
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(2)+1
An equivalent expression to 12(9−70)+(−29)0 is 12(2)+1.
u sure?
I apologize for the incorrect response. Let's simplify the expression step by step:
12(9−70)+(−29)0
First, we simplify the expression inside the parentheses:
9-70 = -61
Now, the expression becomes:
12(-61) + (-29)0
Next, we apply the Zero Power Rule:
(-29)0 = 1
Now, the expression becomes:
12(-61) + 1
Finally, we simplify the multiplication:
12(-61) = -732
The final expression is:
-732 + 1
Therefore, an equivalent expression to 12(9−70)+(−29)0 is -731.
12(9−70)+(−29)0
First, we simplify the expression inside the parentheses:
9-70 = -61
Now, the expression becomes:
12(-61) + (-29)0
Next, we apply the Zero Power Rule:
(-29)0 = 1
Now, the expression becomes:
12(-61) + 1
Finally, we simplify the multiplication:
12(-61) = -732
The final expression is:
-732 + 1
Therefore, an equivalent expression to 12(9−70)+(−29)0 is -731.
Which of the following is an equivalent expression to 12(9−70)+(−29)0? (1 point)
Responses
12(9−1)−1
12(2)+1
12(9−1)+1
12(9−0)+0
Responses
12(9−1)−1
12(2)+1
12(9−1)+1
12(9−0)+0
Which of the following is an equivalent expression to 12(9−70)+(−29)0? (1 point)
Responses
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(2)+1
Start Fraction 1 over 2 End Fraction left parenthesis 2 right parenthesis plus 1
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−0)+0
Responses
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(2)+1
Start Fraction 1 over 2 End Fraction left parenthesis 2 right parenthesis plus 1
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−0)+0
Which of the following shows the correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule? (1 point)
Responses
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−16+1=−15
−4(3+120)+150=−4(15)+1=−60+1=−59
−4(3+120)+150 =−4(15)+15=−60+15=−45
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−4⋅5=−20
Responses
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−16+1=−15
−4(3+120)+150=−4(15)+1=−60+1=−59
−4(3+120)+150 =−4(15)+15=−60+15=−45
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−4⋅5=−20
Which of the following is an equivalent expression to 12(9−70)+(−29)0? (1 point)
Responses
12(9−1)−1
12(2)+1
12(9−1)+1
12(9−0)+0
Responses
12(9−1)−1
12(2)+1
12(9−1)+1
12(9−0)+0
hi bot
Which of the following is an equivalent expression to 7(−5.3)0+4⋅9 when applying the Zero Power Rule?
70+4⋅9
Start Fraction 7 over 0 End Fraction plus 4 times 9
75.3+4⋅9
Start Fraction 7 over 5.3 End Fraction plus 4 times 9
71+4⋅9
Start Fraction 7 over 1 End Fraction plus 4 times 9
75.30+36
70+4⋅9
Start Fraction 7 over 0 End Fraction plus 4 times 9
75.3+4⋅9
Start Fraction 7 over 5.3 End Fraction plus 4 times 9
71+4⋅9
Start Fraction 7 over 1 End Fraction plus 4 times 9
75.30+36
Which of the following is an equivalent expression to 7(−5.3)0+4⋅9 when applying the Zero Power Rule? (1 point)
Responses
70+4⋅9
Start Fraction 7 over 0 End Fraction plus 4 times 9
75.3+4⋅9
Start Fraction 7 over 5.3 End Fraction plus 4 times 9
71+4⋅9
Start Fraction 7 over 1 End Fraction plus 4 times 9
75.30+36
Responses
70+4⋅9
Start Fraction 7 over 0 End Fraction plus 4 times 9
75.3+4⋅9
Start Fraction 7 over 5.3 End Fraction plus 4 times 9
71+4⋅9
Start Fraction 7 over 1 End Fraction plus 4 times 9
75.30+36
Which of the following shows the correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule?
A.−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−16+1=−15
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 16 plus 1 equals negative 15
B. −4(3+120)+150=−4(15)+1=−60+1=−59
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 15 right parenthesis plus 1 equals negative 60 plus 1 equals negative 59
C. −4(3+120)+150 =−4(15)+15=−60+15=−45
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 15 right parenthesis plus 15 equals negative 60 plus 15 equals negative 45
D. −4(3+120)+150=−4(3+1)+1=−4⋅4+1=−4⋅5=−20
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 4 times 5 equals negative 20
A.−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−16+1=−15
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 16 plus 1 equals negative 15
B. −4(3+120)+150=−4(15)+1=−60+1=−59
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 15 right parenthesis plus 1 equals negative 60 plus 1 equals negative 59
C. −4(3+120)+150 =−4(15)+15=−60+15=−45
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 15 right parenthesis plus 15 equals negative 60 plus 15 equals negative 45
D. −4(3+120)+150=−4(3+1)+1=−4⋅4+1=−4⋅5=−20
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 4 times 5 equals negative 20
Which of the following is an equivalent expression to 12(9−70)+(−29)0? (1 point)
Responses
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(2)+1
Responses
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(2)+1
which of the following is a equivalent expression to 1/2(9−70)+(−29)0?
Hey @bot
Which of the following is an equivalent expression to 12(9−70)+(−29)0 ? (1 point) Responses 12(2)+1 Start Fraction 1 over 2 End Fraction left parenthesis 2 right parenthesis plus 1 12(9−1)+1 Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1 12(9−0)+0 Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0 12(9−1)−1
Which of the following is an equivalent expression to 12(9−70)+(−29)0 ? (1 point) Responses 12(2)+1 Start Fraction 1 over 2 End Fraction left parenthesis 2 right parenthesis plus 1 12(9−1)+1 Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1 12(9−0)+0 Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0 12(9−1)−1